Analysis of the Potential of Rafting Sports Tourism in the Parakan Kondang River Kabupaten Sumedang - Arkiman Arkiman; Dewi Susilawati; Dinar Dinangsit; Rizal Ahmad Fauzi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aims to determine the problems of rafting facilities, the surrounding environment and the potential for rafting sports tourism on the famous parakan river of Sumedang regency, rafting itself is a very interesting sport of course also tests adrenaline in every activity, the method in this study uses qualitative with the population of tourists and rafting operators, samples purposive sampling was taken with the material used, namely the MSPDM (Marketability, Sustainability, Participatory, and Disaster ,Mitigation) instrument through interviews or questionnaires analyzed using the Nvivo 12 software application. The results obtained from the Nvivo 12 software application, namely rafting are very potential to be used as a sports tourism object or recreational sports, analysis of the potential for rafting sports tourism on the  parakan kondang river of Sumedang regency can be concluded that rafting is a potential tourism because the water in the parakan kondang will remain stable both when it rains and is dry because it is accommodated by the Jati Gede dam,  with this, it can raise the name of the Sumedang area and also improve the economy of the people in the rafting sports tourism destination.